Pemberdayaan masyarakat desa dalam mengelola konflik sosial di Kabupaten Bone - Muh. Iqbal Latief; Arsyad Genda; Surianto Surianto; Hariashari Rahim (Unri Conference Series: Community Engagement, 2020)
In general, in Bone District there have been conflicts with the background of various factors such as land issues, politics and even those related to religious values and beliefs. Therefore, the goal to be achieved in this service is to increase the knowledge and understanding of the village community on potential conflicts and conflict resolution efforts undertaken. The method used in this training is the provision of knowledge and understanding through lectures and questions and answers, the practice of mapping potential conflicts so that through conflict management training will produce a conflict management document. This activity was carried out from April to September 2019, starting from the formulation of proposals to the preparation of the final activity report. With the tools prepared and formulating conflict management steps that have the potential to occur in the community, the village community will already know and understand conflict management as well as possible.